Young Electoral Perspective Against Money Politics In The 2024 Presidential Election (Case Study In The Village of Right-Wing Poverty, Single Circle) - Henny Sumaiga; Mardian Idris Harahap (Dinasti Research, 2024)
This research aims to explore young voters' perceptions of money politics in the 2024 presidential election in Pangi Village. In the context of local democracy, young voters in Pangi Village have an important role in the election process, but they are also vulnerable to unhealthy political influences. Using a qualitative approach, data was collected through interviews with young voters in Pangi Village to understand how they view to the practice of money politics. The research results show that the majority of young voters are aware of the existence of money politics in the presidential election, voters are more inclined to get information on social media and the role of the family in determining choices and the environment where the young people live. This indicates that there is community involvement in primary socialization through banners, banners have a direct comparison with the environmental system that occurs in society in shaping voter perceptions. The implications of this research support the need for efforts to improve political education, expand access to objective information, and build awareness of the implications of money politics to strengthen democratic integrity.